Development of wireless type K thermocouple temperature measurement - Nor Asiah, Ahmad Sukori (2010)
This project will focus on how to develop a wireless type K Thermocouple temperature measurement. Visual Basic is used as a main programming language to develop a GUI (Graphical User Interface) application. Then, the sensor for this project is a Thermocouple type K. Wireless system is used to interface the GUI and the thermocouple sensor and ZigBee will be used for the wireless. Wireless temperature measurement system is developed using ZigBee communication technology. It overcomes the disadvantages of wired measurement system, such as complicated wiring and difficult maintenance. The wireless sensor networks based on ZigBee has the characteristics of insulation, strong electromagnetic immunity, low power and high accuracy, solving the problem of easy breaking, easy aging, cannot resist high temperature in traditional optical fiber temperature measurement technology, saving the trouble of wiring, ensuring the reliability and safety of the operation. For this project, the temperature measured by the thermocouple is transmitted to the PC by transceiver controlled by ZigBee, and the temperature data is managed by PC. The thermocouple sensor detected temperature change and send the input to software system where the input is converted from current into voltage signal. In GUI application, the data is recorded and manipulated to get the appropriate result